A preliminary in vivo study on the effectivity of electrosurgery as a method of sterilizing non-vital central incisors - Tiu, Janice; Leviste, Carmen; Porter, Irene (Adviser).
The success of an endodontic treatment has three basic requirements. These are proper mechanical debdridement of the root canals, proper sterilization of the root canals, and proper filling of the canals. To sterilize root canals, clinicians of the UP College of Dentistry Department of Endodontics, utilize intracanal medicaments such as camphorated chlorophenol and eugenol, for their non-vital and vital cases, respectively - still, many a time, clinicians come up with positive culture results. In view of this, the reserchers believe that the field of sterilizing root canals can further be explored, to be able to obtain negative culture results that will render root canal cases safe for obturation and restoration. The intention of the researchers is : to determine the effectivity of electrosurgery as a method of sterilizing non-vital central incissors, through a turbidity test and a plate-count method of microbial study. The electrosurgical sterilization procedure (ESSP) was done on non-vital single-rooted central incissors, that yielded positive results in the first culture-taking. The ESSP consisted of a broach, with the correct working length of the root canal, being attached and held in place with a matrix bond to the handpiece of an electrosurgical unit. The broach was inserted into the root canal. With a rotatory up and down motion, the broach was moved in and out for 1 second, followed by a 5-second rest interval. This procedure was done 30 times. After 48 hours, a second culture was taken. The turbidity and plate-count readings taken before and after the ESSP showed the effectivity of the high-frequency electrocoagulating current was applied uniformly to the walls of the root canal, all its organic content became coagulated and destroyed.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Electrosurgery; Mouth -- Surgery; Endodontics